Pengaruh Kinerja Lingkungan, Green Accounting, Dan Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility (Studi Pada Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2022) - Nakita Salsabila T.P; Willy Sri Yuliandhari (AKUNTANSI 45, 2024)
The concept of CSR has become a key area of focus for responsible companies, which voluntarily commit to reducing the negative impacts and increasing the positive impacts of their operations on the environment, society, and the economy. This study aims to investigate the influence of environmental performance, green accounting implementation, and firm size on the level of CSR disclosure among energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. This study employed a purposive sampling technique, selecting 12 leading companies in the energy sector, resulting in a sample size of 60. The collected data were analysed using panel data regression, applying the random effect model method. The analysis results demonstrate that environmental performance, green accounting, and company size collectively exert a significant influence on CSR disclosure. However, when analysed separately, only green accounting exerts a pronounced positive influence on CSR disclosure. This study offers valuable insights into the importance of green accounting in driving CSR disclosure in energy sector companies. The results of this study are expected to contribute to the development of more sustainable and socially responsible business practices, as well as encourage other companies to implement CSR principles in their operations.